Air Pollution Costs in Ukraine - Elena Strukova; Alexander Golub; Anil Markandya (Fondazione Eni Enrico Mattei (FEEM), 2006)
The paper presents estimation of the health losses from urban air pollution in Ukraine. The methodology developed by US EPA and adjusted in Russia for Eastern European transition countries was applied for health risk assessment. PM2.5 was identified as the major source of human health risk, based on experience from the Russian studies. In the absence of reliable computed concentrations of PM2.5, the study was based on monitoring data of total suspended particle (TSP) emissions in Ukraine. Additional cases of mortality and morbidity were calculated based on reporting data on TSP concentration that was recalculated into PM2.5. Then the concentrationresponse function was applied to estimate individual risk. Next, individual risk was applied to the population exposed to the concentration reported for each city included in the analysis (we selected most polluted cities). For each city we considered individual data on baseline mortality and morbidity and population structure. In total, air pollution related mortality represents about 6 percent of total mortality in Ukraine. In Russia the corresponding indicator totals about 4 percent. The relative mortality risk attributed to air pollution calculated per 100 000 population in both countries is about 55-59 cases. Since applied method is sensitive to the primary data uncertainties we conducted sensitivity analysis applying Monte-Carlo method. Economic damage related to mortality risk was estimated at about 4 percent of GDP. There was no relevant WTP study in Ukraine therefore we applied the benefit-transfer method in order to estimate VSL, since mortality attributed to air pollution is major component of health losses (about 94 percent). In order to compare and aggregate mortality and morbidity risks we recalculated them in DALY. Then morbidity represents about 30 percent of total air pollution health load. Data on baseline morbidity is less reliable than data on baseline mortality; therefore the morbidity risk estimates are more uncertain than mortality estimates. It is likely that morbidity risk is underestimated. Regardless of uncertainties mentioned above and some problems with reported data we can conclude that the mortality risk attributed to air pollution is significant. Therefore, costs of air pollution in Ukraine are sizable and in the nearest future may offset the economic growth. Recovery of the Ukrainian economy based on restoration of polluting industries may lead to stagnation since mortality and morbidity risks not only puts burden on the economy, but also reduce labor force.
Keywords: Q53; I10; I18; 330; Air Pollution; Ukraine; Environmental Damages; Luftverunreinigung; Wohlfahrtsanalyse; Gesundheitsrisiko; Ukraine